2012
DOI: 10.1016/j.arth.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Interface Micromotion of Uncemented Femoral Components from Postmortem Retrieved Total Hip Replacements

Abstract: Axial torsional loads representative of gait and stair climbing conditions were applied to transverse sections of 8 uncemented postmortem retrievals and a high-resolution imaging system with digital image correlation was used to measure local micromotion along the bone-implant interface. For seven components that were radiographically stable, there was limited micromotion for gait loading (1.42±1.33 μm) that increased significantly (p=0.0032) for stair climb loading (7.32±9.96 μm). A radiographically loose com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…We found higher micromotion in torsion (stair climbing) than in compression (walking). This result compares well with results from Enoksen et al (2014) and Kassi et al (2005) obtained with LVDTs or with measurements from postmortem retrieval sections by Mann et al (2012). The patterns of micromotion revealed that for axial compression, micromotion was low proximally and high distally.…”
Section: Discussionsupporting
confidence: 77%
“…We found higher micromotion in torsion (stair climbing) than in compression (walking). This result compares well with results from Enoksen et al (2014) and Kassi et al (2005) obtained with LVDTs or with measurements from postmortem retrieval sections by Mann et al (2012). The patterns of micromotion revealed that for axial compression, micromotion was low proximally and high distally.…”
Section: Discussionsupporting
confidence: 77%
“…We developed a new in vitro model for bone implant loosening, which is able to simulate supraphysiological loading as it occurs in the peri‐prosthetic interface in patients undergoing prosthetic revision surgery, but also determined using human samples post‐mortem . In this new model, we demonstrated that similar pathophysiological mechanisms are involved in overloading‐induced and stress‐shielding related bone loss, which have been discussed previously in animal models for instability‐induced prosthetic loosening, where a high fluid flow rate at the peri‐implant surface was associated with enhanced osteoclast differentiation and bone loss .…”
Section: Discussionmentioning
confidence: 68%
“…Soluble factors were released in the conditioned medium after treatment of the cells with this supraphysiological loading regime, which induced osteoclast differentiation. The main difference between the sinusoidal and square wave loading regimes used in this study are the flow velocity and the shear stress rate, which play an important role in the activation of bone cells, as well as in the loosening of prostheses …”
Section: Discussionmentioning
confidence: 99%
“… 16 The relationship between bone-implant contact and micromotions was also demonstrated on transverse sections of retrievals of uncemented hips under gait and stair-climbing test conditions. 29 It was also observed that micromotions alter osteoblast activity. However, it is not only the question of whether bone formation is taking place but also of how the bone is remodelled and the bone architecture altered in the implant periphery.…”
Section: Discussionmentioning
confidence: 99%